AFFINITY AND REACTIVITY STUDIES OF THE REACTION OF HUMAN (Homo sapiens) AND CAT (Felis catus) HAEMOGLOBINS WITH 5,5´-DITHIOBIS(2-NITROBENZOATE) (2014)
Some haemoglobins have high oxygen affinity (high-affinity) while others have low oxygen affinity (low-affinity) as exemplified in human and cat haemoglobins respectively. High-affinity haemoglobins bind organic phosphates strongly and this lowers their oxygen affinities and their CysF9[93]? sulphydryl reactivities. Low-affinity haemoglobins on the other hand, bind organic phosphates weakly, and their oxygen affinities are hardly affected. Consequently, an assumption which is yet to be verified is that the reactivity of their CysF9[93]? is not affected by organic phosphates. Furthermore, the reaction of 5,5´- dithiobis(2-nitrobenzoate) - DTNB - with CysF9[93]? of haemoglobins in the relaxed quaternary conformation has been found to be reversible but this is yet to be determined in the tense quaternary conformation. This research was therefore aimed at studying the effect of organic phosphate-binding on low-affinity cat haemoglobins and the reversibility of the reaction of DTNB with human deoxyhaemoglobin. The major and minor haemoglobins in cat haemolysate were separated on a column of carboxymethylcellulose. Human oxyhaemoglobin was isolated from blood using standard laboratory techniques. Solutions of deoxyhaemoglobin were prepared by passing humidified nitrogen gas over an aliquot of oxyhaemoglobin. Pseudo-first order kinetics of the reaction of DTNB with the CysF9[93]? sulphydryl of human and cat haemoglobins were studied at 25°C. The DTNB concentration was varied while that of the sulphydryl was kept constant. The second order rate constants, kF, were obtained from linear plots of the pseudo-first order rate constant, kobs, versus the DTNB concentration. Equilibrium experiments were performed by adding 3 cm3 of a 50 ?mol (haem) dm-3 haemoglobin solution into varying volumes of a stock 29 mmol dm-3 DTNB solution inside test tubes. The mixtures were equilibrated at 25°C for 6 to 8 hours. The absorbances of these mixtures were measured at 412 nm, using a UV-visible spectrophotometer, and substituted into an equation derived to determine the equilibrium constant, Kequ, of the reaction. All experiments were carried out between pH 5.6 and 9.0 for both the stripped and inositol hexakisphosphate (inositol-P6)-bound haemoglobin. Data were analysed using descriptive statistics. The percentages of major and minor haemoglobins in cat haemolysate were 60.0 ± 4.0 and 40.0 ± 4.0 respectively. Plots of kobs at constant pH against the DTNB concentration were linear. The plots had positive intercepts for deoxyhaemoglobin, indicating that its reaction with DTNB is reversible. Stripped human oxyhaemoglobin gave a bell-shaped pH-dependence profile for kF, with a maximum value of 31.9 ± 0.6 mol-1dm3s-1 at pH 7.1. In the presence of inositol-P6, kF decreased. In contrast, cat haemoglobins gave simple pH-dependence profiles. Inositol-P6 increased kF by about two-fold throughout the experimental pH range. The Kequ increased in the presence of inositol-P6 for both cat haemoglobins and human deoxyhaemoglobin. This is an indication of increased affinity for DTNB in both haemoglobins. The affinity of deoxyhaemoglobin for DTNB was also higher compared to that of oxyhaemoglobin. The CysF9[93]? of low-affinity cat haemoglobins had their reactivities increased by inositol hexakisphosphate. The reaction of 5,5´-dithiobis(2-nitrobenzoate) with haemoglobin was reversible in the tense quaternary structure.